BK POLYOMAVIRUS AS THE CAUSE OF HEMORRHAGIC CYSTITIS IN PATIENTS TREATED WITH ALLOGENEIC STEM CELL TRANSPLANTATION - Stankovic, Stefan; Đunić, Irena (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: BK polyomavirus is a double-stranded DNA virus from the Polyomaviridae family. According to DNA sequences, this virus can be classified into six genotypes. In hematological patients enrolled in allogeneic hematopoietic stem cell transplantation (HSCT) programs, it can lead to hemorrhagic cystitis. Aim: The aim of this study is calculating the prevalence of BK polyomavirus PCR (polymerase chain reaction) positivity in the blood and urine of patients involved in allogeneic HSCT, determining the predictive factors for clinical presentation of BK polyomavirus-associated hemorrhagic cystitis, as well as determining its effects on overall survival (OS) of the patients.Materials and methods: This retrospective cohort study enrolled 42 patients from the Clinic of Hematology of the University Clinical Center of Serbia. The presence of the virus in blood and urine was determined by the PCR method. The survival rate of the patients in relation to hemorrhagic cystitis was calculated with the Kaplan-Meier method and comparison was performed with the log-rank test.Results: A positive PCR result in the blood was found in 97.6% of the subjects, while urine tested positive in 100% of patients. The estimated survival time in patients without hemorrhagic cystitis was 44.357 months, while the group with the clinical presentation of hemorrhagic cystitis had an estimated survival time of 17.395 months. Based on the log-rank test, we found a significant difference in survival between those groups of patients (p = 0.049). With regards to leukocyte engraftment day, patients engrafted after D+14, had a higher frequency of hemorrhagic cystitis (p = 0.037).Conclusion: BK polyomavirus-associated hemorrhagic cystitis is a common complication of treatment in patients suffering from hematological malignancies who are enrolled in an alo-HSCT program, and has a significant impact on OS.
Keywords: allogeneic HSCT; BK polyomavirus; hemorrhagic cystitis